2022
DOI: 10.1590/s2175-97902022000x2e19212
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of asarone removal from Piper sarmentosum Roxburgh leaves using supercritical carbon dioxide extraction: the Box-Behnken design

Abstract: Piper sarmentosum is a herbaceous shrub with numerous pharmacological benefits. However, the presence of two toxic phenylpropanoids (α-and β-asarone) limits the medicinal usage of the plant. In this study, the extraction of three asarone isomers, namely α-, β-, and ɣ-asarone was optimised using supercritical carbon dioxide extraction (SC-CO 2 ) combined with Box-Behnken experimental design. Comparison of asarone contents in different conventional solvent extracts of P. sarmentosum leaves prior to and after SC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…Vuong and Roach (2014) also reported that functional polyphenolics such as catechins were maintained and preserved in green tea after decaffeination using SC-CO 2 . Our previous study successfully produced an asarones-free (α-, β-and γ-asarones) ethanol extract using the two-step extraction technique (Hamil et al, 2022). The present study showed that SC-CO 2 pre-treatment could retain and enhance the quantity of other beneficial components in the sample material, such as polyphenols and flavonoids, apart from removing unwanted compounds.…”
Section: Enhancement Of Phenolics and Flavonoids In Sc-co 2 Pre-treat...mentioning
confidence: 59%
See 2 more Smart Citations
“…Vuong and Roach (2014) also reported that functional polyphenolics such as catechins were maintained and preserved in green tea after decaffeination using SC-CO 2 . Our previous study successfully produced an asarones-free (α-, β-and γ-asarones) ethanol extract using the two-step extraction technique (Hamil et al, 2022). The present study showed that SC-CO 2 pre-treatment could retain and enhance the quantity of other beneficial components in the sample material, such as polyphenols and flavonoids, apart from removing unwanted compounds.…”
Section: Enhancement Of Phenolics and Flavonoids In Sc-co 2 Pre-treat...mentioning
confidence: 59%
“…Dried powdered leaves (50 g) were extracted using a 1-litre SC-CO 2 extractor (Separex, France). The experimental parameters were set according to the method established by Hamil et al (2022): pressure = 81.16 bar, temperature = 50.11°C and dynamic extraction time = 80.90 min. The flow rate was maintained at 30 g/min, and the static extraction time was fixed at 30 min.…”
Section: Treatment Of P Sarmentosum Leaves Using Sc-comentioning
confidence: 99%
See 1 more Smart Citation